2016
DOI: 10.1007/978-3-319-49052-6_2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-core SCC-Based LTL Model Checking

Abstract: We investigate and improve the scalability of multi-core LTL model checking. Our algorithm, based on parallel DFS-like SCC decomposition, is able to efficiently decompose large SCCs on-the-fly, which is a difficult problem to solve in parallel.To validate the algorithm we performed experiments on a 64-core machine. We used an extensive set of well-known benchmark collections obtained from the BEEM database and the Model Checking Contest. We show that the algorithm is competitive with the current state-ofthe-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Recall that our notion of causality relies on the complete enumeration of system traces. Hence, the main challenge is to determine all (lasso-shaped) counterexamples in an efficient way (e.g., on-the-fly [8,24,3,4]). Further future research comprises significant case studies in order to asses the scalability of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…Recall that our notion of causality relies on the complete enumeration of system traces. Hence, the main challenge is to determine all (lasso-shaped) counterexamples in an efficient way (e.g., on-the-fly [8,24,3,4]). Further future research comprises significant case studies in order to asses the scalability of our approach.…”
Section: Discussionmentioning
confidence: 99%
“…With current hardware systems, one can further improve the model checking performance by using multiple cores. This way, the time to model check can be significantly reduced; related work shows that even though the problem is difficult to parallelize, in practice an almost linear improvement with respect to the number of cores can be obtained [8,16,20,32].…”
Section: Model Checkingmentioning
confidence: 99%
“…Our objective is to study whether the speedups observed with TGRAs in probabilistic model checking also hold for non-probabilistic explicit model checking. There are plenty of algorithms for checking BAs and TGBAs (both sequentially and multi-core) [8,16,32,33]; however, for Rabin acceptance there is only a recent work on a GPU algorithm for checking (non-generalized) RAs [35] and a TGRA checking algorithm for probabilistic model checking [9].…”
Section: Our Goal: Emptiness Checks Using Generalized Rabin Automatamentioning
confidence: 99%
“…In case we want to know whether an LTS satisfies a formula φ, the product of an LTS and a Büchi automaton of Words(φ) is computed, while checking for a witness that visits an accepting state in the Büchi automaton infinitely often. Searching for such a witness can be done on-the-fly [9] with (concurrent) nested depth-first search [8,25] or SCC-based approaches [5,42].…”
Section: Black-box Checking With Model Checkingmentioning
confidence: 99%
“…The counterexamples are finite words and are a subset of the language of the hypothesis. LTSmin [5,22] is an available implementation of a ModelChecker for Monitors in the LearnLib. A ModelCheckerLasso is a refinement of a ModelChecker that uses Büchi automata and where the counterexamples are lassos instead of finite words.…”
Section: The New Api In the Learnlibmentioning
confidence: 99%